The Qur’ān in Medieval Slavic Writings. Fragmentary Translations and Transmission Traces - Brzozowska, Zofia A.; Leszka, Mirosław J. (Vox Patrum, 2022)
The Qur’ān was never translated into Church Slavic in its entirety; still, in the writings of some mediaeval Christian authors (Byzantine and Latin) quite extensive quotations and borrowings from it can be found. Many of these texts were transmitted in the Slavia Orthodoxa area. The aim of this article is to present the Church Slavic literary sources which contain quotations from the Qur’ān. The analysis covers Slavic translations of Byzantine and Latin authors as well as original texts of Slavic provenance. The main conclusion of the research is that only ca. 2% of the text of the Qur’ān has been preserved in the Church Slavic material.